Preparation method of full-bio-based foaming material and foaming material

By grafting L-polylactic acid (PLA) onto cellulose nanocrystals and then onto D-polylactic acid (PLA), an interfacial stereocomposite crystal is formed, which solves the problem of insufficient thermal insulation and mechanical properties of existing PLA foam materials and produces a high-performance, fully bio-based foam material suitable for food packaging and building materials.

CN121379071APending Publication Date: 2026-01-23NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511386791.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare polylactic acid foam materials that are easy to operate and have both excellent thermal insulation and mechanical properties. The reinforcing effect of cellulose nanocrystals is limited, the cell structure is difficult to control precisely, and the equipment is complex and costly.

Method used

A method of grafting L-polylactic acid with cellulose nanocrystals onto D-polylactic acid was adopted. Through compression molding and carbon dioxide foaming, an interfacial stereocomposite crystal was formed, which served as the nucleation site for cell formation. Multiple parameters of the foaming process were controlled to prepare a bimodal cell structure.

Benefits of technology

This fully bio-based foam material achieves high foaming ratio, excellent thermal insulation and mechanical properties, and is suitable for food packaging and building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121379071A_ABST
    Figure CN121379071A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a full bio-based foaming material, which comprises the following steps: S1, dissolving 90-99 parts by weight of L-polylactic acid and 1-10 parts by weight of cellulose nanocrystal grafted D-polylactic acid in an organic solvent a, fully stirring, and desolventizing at 20-80 DEG C to obtain a polylactic acid / cellulose nanocrystal composite material; the length-diameter ratio of the cellulose nanocrystal is 15 to 30; s2, placing the polylactic acid / cellulose nanocrystalline composite material in a press vulcanizer for compression molding to obtain a sheet; and S3, placing the sheet in carbon dioxide gas, heating to a saturation temperature for saturation treatment, then cooling to a foaming temperature, and immediately releasing the pressure to normal pressure for foaming to obtain the full-bio-based foaming material. The full-bio-based foaming material prepared by the preparation method has excellent heat-insulating property and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of foaming material technology, specifically relating to a method for preparing a fully bio-based foaming material and the foaming material itself. Background Technology

[0002] Polylactic acid (PLA) is a bio-based and biodegradable polymer material. Due to its advantages such as good biocompatibility, high mechanical strength, and good processability, it is considered one of the most promising bio-based plastics. PLA foam materials, in addition to their already superior properties, possess special functions such as lightweight, sound and heat insulation, and shock absorption, showing great application potential in packaging, construction, tableware materials, and tissue scaffolds. However, due to its low melt strength, PLA has poor foaming ability, resulting in foam materials with problems such as large cell size, severe cell deformation, and low mechanical strength. Furthermore, PLA has a slow crystallization rate, leading to low crystallinity in its foam materials and consequently poor heat resistance. Adding nanofillers can not only simultaneously improve the melt strength and crystallization rate of PLA but also strengthen PLA foam materials. Among many nanofillers such as carbon nanotubes and graphene, nanocellulose, due to its bio-based origin, does not affect the bio-based properties of PLA and is one of the best nanofillers for improving the performance of PLA foam materials.

[0003] Patent application CN107383434B discloses a method for preparing a cellulose nanocrystal-reinforced polylactic acid (PLA) foam material. The method involves uniformly mixing cellulose nanocrystals and PLA in a solvent and then foaming with supercritical carbon dioxide to obtain the cellulose nanocrystal-reinforced PLA foam material. This application improves the mechanical properties of the material by blending cellulose nanocrystals and PLA and then using supercritical CO2 foaming technology. However, this method does not improve the interfacial forces between PLA and cellulose nanocrystals, thus limiting the reinforcing effect of cellulose nanocrystals, and it does not involve fine control of the cell structure.

[0004] Patent application CN116178777B discloses a thermal insulation foam material with a bimodal pore structure and its preparation method. The preparation method includes: preparing semi-crystalline polymer / cellulose nanofiber composite particles by extruding a semi-crystalline polymer and a modified or unmodified cellulose nanofiber aqueous solution through a twin-screw extruder, or further molding the particles into sheets; subjecting the obtained particles or sheets to a two-stage fluid saturation treatment in a foaming gas, wherein the crystals in the particles or sheets are completely melted at the temperature of the first saturation stage, and the temperature of the second saturation stage is the crystallization temperature of the particles or sheets; and foaming the treated particles or sheets to obtain a thermal insulation foam material with a bimodal pore structure.

[0005] This application utilizes cellulose nanofibers as nucleating agents to improve the foaming properties of polylactic acid (PLA). Simultaneously, by controlling the temperature at different saturation stages and leveraging the differences in polymer crystallization rates, a foamed material with a bimodal cell structure was successfully prepared. Compared to microporous materials with a single-size distribution, the bimodal cell structure exhibits superior mechanical properties, sound insulation, and thermal insulation performance. However, this application has significant drawbacks: the cellulose nanofibers used have a high aspect ratio, readily forming a network structure, which to some extent limits cell growth during the foaming process, making it difficult to further increase the foaming ratio and thus limiting the improvement in thermal insulation performance; secondly, the formation of the bimodal structure strongly depends on a two-stage saturation process, requiring sophisticated equipment and control, increasing process complexity and cost.

[0006] Therefore, developing a simple method for preparing foamed materials that can produce materials with excellent thermal insulation and mechanical properties has become a critical issue that urgently needs to be addressed. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the first aspect of this invention provides a method for preparing a fully bio-based foamed material. The fully bio-based foamed material prepared by this method has both excellent thermal insulation and mechanical properties, and the preparation method is simple to operate.

[0008] The method for preparing the all-bio-based foam material provided by this invention includes: S1. Dissolve 90-99 parts of L-polylactic acid and 1-10 parts of cellulose nanocrystal-grafted D-polylactic acid in organic solvent a according to the weight ratio, stir thoroughly, and desolvent at 20-80℃ to obtain polylactic acid / cellulose nanocrystal composite material, wherein the aspect ratio of the cellulose nanocrystal is 15-30. S2. The polylactic acid / cellulose nanocrystalline composite material is placed in a flat vulcanizing machine for compression molding to obtain a sheet; S3. Place the sheet in carbon dioxide gas, heat it to the saturation temperature for saturation treatment, then cool it to the foaming temperature, and immediately depressurize it to normal pressure for foaming to obtain the fully bio-based foamed material.

[0009] This invention involves grafting dextrorotatory polylactic acid (DLA) onto the surface of cellulose nanocrystals, followed by blending with a levorotatory polylactic acid (LLA) matrix. The DLA on the cellulose nanocrystal surface forms stereocomposite crystals distributed at the interface with the LLA matrix in situ. Both the stereocomposite crystals and the cellulose nanocrystals serve as nucleation sites for cell formation during the foaming process, exhibiting a dual nucleation effect. The resulting fully bio-based foamed material exhibits a bimodal distribution in cell size. Larger cells increase the foaming ratio, enhance thermal insulation performance, and reduce material weight, while smaller cells increase the specific compressive modulus and improve the material's mechanical properties.

[0010] Moreover, compared to cellulose nanofibers with a large aspect ratio, this invention uses cellulose nanocrystals within a moderate aspect ratio range as nanofillers for polylactic acid, enabling the production of foamed materials with a higher expansion ratio, thereby improving the thermal insulation performance of the foamed materials. This not only avoids the problem of insufficient melt strength enhancement for polylactic acid due to an excessively small aspect ratio, which could cause cell rupture or merging during growth, insufficient to support cell structure growth and limit the expansion ratio; but also avoids the problem of nanofillers entangled and forming a network structure due to an excessively long aspect ratio, which would also inhibit cell growth and reduce the expansion ratio.

[0011] Secondly, the stereocomposite crystals distributed at the interface can improve the dispersion uniformity of cellulose nanocrystals in polylactic acid melt. Uniformly dispersed cellulose nanocrystals can improve the melt strength of polylactic acid, increase the foaming ratio, and provide more nucleation sites, resulting in smaller cell size. Smaller cell size can increase the specific compressive modulus of the foam material, thereby improving mechanical properties. On the other hand, it can increase the interfacial force between the polylactic acid matrix and cellulose nanocrystals, promote stress transfer between the two, and help to better exert the mechanical reinforcing effect of cellulose nanocrystals on polylactic acid.

[0012] Furthermore, the interfacial stereocomposite crystals and well-dispersed cellulose nanocrystals can jointly promote the crystallization of polylactic acid, resulting in high crystallinity of the prepared foam material, thereby improving its heat resistance.

[0013] This invention also controls the weight ratio of L-polylactic acid and cellulose nanocrystal-grafted D-polylactic acid to obtain a foamed material with a more balanced thermal insulation and mechanical properties. This avoids the situation where excessive addition of cellulose nanocrystal-grafted D-polylactic acid, even if a sufficient amount of stereocomposite crystals can be generated, will lead to excessive reinforcement of the polylactic acid melt by the cellulose nanocrystals, restricting cell growth, thereby reducing the foaming rate, increasing thermal conductivity, and limiting the thermal insulation effect of the foamed material. At the same time, it avoids the situation where insufficient addition of cellulose nanocrystal-grafted D-polylactic acid fails to effectively exert the reinforcing effect of cellulose nanocrystals on polylactic acid, and the performance of the foamed material cannot be effectively improved.

[0014] Preferably, in step S1, the proportion of L-polylactic acid is 97-98.5 parts by weight, and the proportion of cellulose nanocrystals grafted with D-polylactic acid is 1.5-3 parts.

[0015] This invention, by further controlling the weight ratio of L-polylactic acid and cellulose nanocrystals grafted with D-polylactic acid, yields a fully bio-based foam material with more balanced thermal insulation and mechanical properties, wherein the thermal conductivity is 31~32.5 mW·m. -1 ·K -1 The specific compressive modulus is 160~180 MPa / g·cm.3 .

[0016] In step S1, the weight-average molecular weight of the L-polylactic acid is 5 × 10⁻⁶. 4 ~5×10 5 g / mol, optical purity ≥97%.

[0017] In step S1, the organic solvent a is chloroform or dichloroform.

[0018] In step S2, the molding temperature is 170~210 ℃ and the pressure is 5~15 MPa.

[0019] In step S2, the thickness of the sheet is 0.3~3 mm.

[0020] In step S3, the pressure of the carbon dioxide gas is 5~25 MPa, the saturation temperature is 150~190 ℃, the saturation time is 3~30 min, and the foaming temperature is 80~130 ℃.

[0021] In step S3, during the process of cooling from the saturation temperature to the foaming temperature, the cooling rate is 2~30℃ / min.

[0022] In step S3, the depressurization rate of the depressurization foaming is 5~60 MPa / s.

[0023] This invention controls multiple parameters, including the heating and cooling rates and the depressurization rate, during the foaming process of the sheet material to induce the formation of a bimodal cell structure, thereby producing a fully bio-based foam material with both excellent thermal insulation and mechanical properties.

[0024] In step S1, the method for preparing the cellulose nanocrystals grafted with dextrorotatory polylactic acid includes: (1) Cellulose nanocrystals and dextrorotatory lactide were uniformly dispersed in organic solvent b at a weight ratio of 1:3 to 1:30. After being mixed evenly, a catalyst was added. The reaction temperature was 70 to 110 °C, and the reaction was carried out under nitrogen protection for 12 to 36 h to obtain the reactants. (2) Dissolve the reactants in chloroform and purify by centrifugation to obtain the cellulose nanocrystal grafted dextrorotatory polylactic acid.

[0025] The method for preparing cellulose nanocrystal-grafted polylactic acid provided by the present invention involves reacting cellulose nanocrystals with an excess of dextrorotatory lactide. Utilizing the hydroxyl groups of the cellulose nanocrystals, in-situ ring-opening polymerization is used to initiate the ring-opening of dextrorotatory lactide, resulting in a sufficient amount of cellulose nanocrystal-grafted polylactic acid. Furthermore, a stereocomposite crystal is formed at the interface. The stereocomposite crystal and cellulose nanocrystals not only promote the generation of bimodal cells in the subsequent foaming material but also increase the foaming ratio, thus helping to improve the thermal insulation, mechanical, and heat resistance properties of the foaming material.

[0026] In step (1), the organic solvent b is toluene or xylene.

[0027] In step (1), the catalyst is stannous octoate or stannous isooctanoate, and the amount of the catalyst used is 0.5% to 4% of the weight fraction of dextrorotatory lactide.

[0028] Preferably, in step (2), the grafting rate of the dextrorotatory polylactic acid is 15~35 wt%.

[0029] Secondly, the present invention also provides a fully bio-based foam material prepared by the method for preparing the fully bio-based foam material.

[0030] The fully bio-based foaming material provided by this invention has a bimodal foam structure, possessing both a micropore structure with a pore size distribution between 20 and 40 μm and a macropore structure with a pore size distribution between 100 and 140 μm.

[0031] The fully bio-based foaming material consists of polylactic acid and cellulose nanocrystals, both of which are bio-based and biodegradable, conforming to the concept of green environmental protection.

[0032] The thermal conductivity of the all-bio-based foam material is 31~36 mW·m. -1 ·K -1 The specific compression modulus is 150~220 MPa / g·cm. 3 .

[0033] Moreover, the fully bio-based foamed material provided by this invention has high foaming ratio, thermal insulation performance, heat resistance performance and specific compression modulus, and can be widely used in the fields of food packaging and building materials.

[0034] Compared with the prior art, the present invention has the following beneficial effects: This invention first grafts dextrorotatory polylactic acid (PLA) onto the surface of cellulose nanocrystals, and then blends it with a levorotatory PLA matrix. The PLA on the surface of the cellulose nanocrystals forms stereocomposite crystals distributed at the interface with the levorotatory PLA matrix in situ. On the one hand, since both the stereocomposite crystals and the cellulose nanocrystals can serve as nucleation sites for foaming, a dual nucleation effect is formed, giving the foamed material a bimodal pore structure, thereby improving the thermal insulation and mechanical properties of the foamed material. On the other hand, using cellulose nanocrystals with a suitable aspect ratio as nanofillers for PLA can increase the foaming ratio, thereby improving the thermal insulation performance of the foamed material.

[0035] Furthermore, the stereocomposite crystals distributed at the interface can improve the dispersion uniformity of cellulose nanocrystals in polylactic acid melt, enhance the strength of polylactic acid melt, improve mechanical properties and foaming ratio, and simultaneously strengthen the interfacial bonding force between cellulose nanocrystals and polylactic acid, thus more effectively leveraging the mechanical reinforcing effect of cellulose nanocrystals on polylactic acid. The aforementioned interfacial stereocomposite crystals and well-dispersed cellulose nanocrystals also jointly promote the crystallization of polylactic acid, resulting in high crystallinity in the prepared foam material, thereby improving heat resistance.

[0036] The present invention also provides a foamed material with relatively balanced thermal insulation and mechanical properties by providing a suitable weight ratio of L-polylactic acid and cellulose nanocrystal grafted with D-polylactic acid. Attached Figure Description

[0037] Figure 1 This is a scanning electron microscope (SEM) image of the pure polylactic acid foam material prepared in Comparative Example 1 of this invention.

[0038] Figure 2 The infrared spectrum of cellulose nanocrystals grafted with dextrorotatory polylactic acid in Example 1 of this invention is shown.

[0039] Figure 3 This is a scanning electron microscope (SEM) image of the all-bio-based foam material prepared in Example 1 of the present invention. Detailed Implementation

[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0041] It is worth noting that: (1) The SEM images of the foam samples in the following examples and comparative examples were obtained by a German ZEISS scanning electron microscope.

[0042] (2) The expansion ratio of the foam samples obtained in the following examples and comparative examples is obtained by density conversion. The expansion ratio Φ = ρ f / ρ s , where ρ s and ρ f The densities of the unfoamed and foamed materials are respectively, measured using the water displacement method according to ISO 1183-1987 standard. Cell size and cell density were measured and calculated using ImageJ software. The cell density N (unit: cells / cm³) is also shown. 3 )=(n / A) 3 / 2 Φ and n represent the number of pores on the selected scanning electron microscope, and A represents the actual area of ​​the scanned image (unit: cm²). 2 ).

[0043] (3) The crystallinity of the foam samples obtained in the following examples and comparative examples was measured by a differential scanning calorimeter by Mettler of Switzerland, with a heating rate of 10 °C / min.

[0044] (4) The heat resistance data of the foam samples obtained in the following examples and comparative examples were obtained by testing with a 50 g weight in a constant temperature drying oven at a certain temperature.

[0045] (5) The specific compression modulus of the foam samples obtained in the following examples and comparative examples is the ratio of compression modulus to foam density, wherein the compression modulus is obtained according to the standard ASTM D1621–2010.

[0046] (6) The thermal conductivity of the foam samples obtained in the following examples and comparative examples was obtained by testing with a thermal constant meter at room temperature.

[0047] Example 1 Example 1 of this invention provides a fully bio-based foaming material, which is prepared by the following method: S1. 98 parts of L-polylactic acid (weight average molecular weight 1.70 × 10⁻⁶) 5 Two parts of cellulose nanocrystal-grafted dextrorotatory polylactic acid (PLA) with an optical purity of 99.1% (g / mol) and cellulose nanocrystal grafted dextrorotatory polylactic acid were dissolved in chloroform according to the weight ratio and stirred thoroughly. The solvent was removed at 30 °C to obtain a polylactic acid / cellulose nanocrystal composite material. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 190 °C and 10 MPa to obtain a sheet with a thickness of 1.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 10 MPa, heat it to 165 ℃ for saturation treatment for 10 min, then cool it down to 110 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to normal pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0048] The preparation method of cellulose nanocrystal grafted with dextrorotatory polylactic acid as described in Example 1 of this invention is as follows: (1) Cellulose nanocrystals (aspect ratio of 20) and dextrorotatory lactide were uniformly dispersed in toluene at a weight ratio of 1:10. After the two solutions were mixed evenly, stannous octoate catalyst (2% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 80℃ under nitrogen protection for 24 h. The reaction was then completed. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanocrystals grafted with dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 21.5 wt%.

[0049] Figure 2 The image shows the infrared spectrum of cellulose nanocrystals grafted with dextrorotatory polylactic acid obtained in Example 1 of this invention. Figure 3 This is a scanning electron microscope (SEM) image of the all-bio-based foam material prepared in Example 1 of the present invention.

[0050] Example 2 Example 2 of this invention provides a fully bio-based foaming material, which is prepared by the following method: S1. 97 parts of L-polylactic acid (weight average molecular weight 1.70 × 10⁻⁶) 5 The polylactic acid (PLA) and 3 parts of cellulose nanocrystal grafted with dextrorotatory polylactic acid (PLA) were dissolved in chloroform according to the weight ratio and stirred thoroughly. The solvent was removed at 40 °C to obtain the PLA / cellulose nanocrystal composite material. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 200 °C and 10 MPa to obtain a sheet with a thickness of 1.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 15 MPa, heat it to 165 ℃ for saturation treatment for 10 min, then cool it down to 110 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to atmospheric pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0051] The preparation method of cellulose nanocrystal grafted with dextrorotatory polylactic acid as described in Example 2 of this invention is as follows: (1) Cellulose nanocrystals (aspect ratio of 20) and dextrorotatory lactide were uniformly dispersed in toluene at a weight ratio of 1:8. After the two solutions were mixed evenly, stannous octoate catalyst (3% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 100 °C under nitrogen protection for 18 h. The reaction was then completed. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanocrystal grafted dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 18.7 wt%.

[0052] Example 3 Example 3 of this invention provides a fully bio-based foaming material, which is prepared by the following method: S1. 99 parts of L-polylactic acid (weight average molecular weight 2.14 × 10⁻⁶) 5 Polylactic acid (PLA) with an optical purity of 99.2% and 1 part of cellulose nanocrystal grafted dextrorotatory polylactic acid were dissolved in dichloromethane according to the weight ratio and stirred thoroughly. The solvent was then removed at 30 °C to obtain a polylactic acid / cellulose nanocrystal composite material. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 190 °C and 12 MPa to obtain a sheet with a thickness of 1 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 10 MPa, heat it to 170 ℃ for saturation treatment for 15 min, then cool it down to 105 ℃ at a rate of 5 ℃ / min, and immediately depressurize it to normal pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0053] The preparation method of cellulose nanocrystal grafted with dextrorotatory polylactic acid as described in Example 3 of this invention is as follows: (1) Cellulose nanocrystals (aspect ratio of 25) and dextrorotatory lactide were uniformly dispersed in xylene at a weight ratio of 1:12. After the two solutions were mixed evenly, stannous isooctanoate catalyst (2% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 110 °C under nitrogen protection for 12 h. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanocrystals grafted with dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 24.8 wt%.

[0054] Example 4 Example 4 of this invention provides a fully bio-based foaming material, which is prepared by the following method: S1. 95 parts of L-polylactic acid (weight average molecular weight 1.70 × 10⁻⁶) 5 Polylactic acid (PLA) with an optical purity of 99.1% and 5 parts of cellulose nanocrystal grafted with dextrorotatory polylactic acid were dissolved in chloroform according to the weight ratio and stirred thoroughly. The solvent was then removed at 50 °C to obtain a polylactic acid / cellulose nanocrystal composite material. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 195 ℃ and 10 MPa to obtain a sheet with a thickness of 2 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 8 MPa, heat it to 160 ℃ for saturation treatment for 20 min, then cool it down to 110 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to atmospheric pressure at a rate of 40 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0055] The preparation method of cellulose nanocrystal grafted with dextrorotatory polylactic acid as described in Example 4 of this invention is as follows: (1) Cellulose nanocrystals (aspect ratio of 30) and dextrorotatory lactide were uniformly dispersed in toluene at a weight ratio of 1:20. After the two solutions were mixed evenly, stannous octoate catalyst (3% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 70 °C under nitrogen protection for 36 h. The reaction was then completed. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanocrystal grafted dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 31.5 wt%.

[0056] Example 5 Example 5 of this invention provides a fully bio-based foaming material, which is prepared by the following method: S1. 98 parts of L-polylactic acid (weight average molecular weight 1.52 × 10⁻⁶) 5 Polylactic acid (PLA) with an optical purity of 98.5% (g / mol) and 2 parts of cellulose nanocrystal grafted dextrorotatory polylactic acid were dissolved in dichloromethane according to the weight ratio and stirred thoroughly. The solvent was then removed at 30 °C to obtain a polylactic acid / cellulose nanocrystal composite material. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 185 ℃ and 10 MPa to obtain a sheet with a thickness of 1.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 20 MPa, heat it to 165 ℃ for saturation treatment for 8 min, then cool it down to 100 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to atmospheric pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0057] The preparation method of cellulose nanocrystal grafted with dextrorotatory polylactic acid as described in Example 5 of this invention is as follows: (1) Cellulose nanocrystals (aspect ratio of 15) and dextrorotatory lactide were uniformly dispersed in toluene at a weight ratio of 1:15. After the two solutions were mixed evenly, stannous octoate catalyst (3% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 80℃ under nitrogen protection for 24 h. The reaction was then completed. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanocrystals grafted with dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 25.2 wt%.

[0058] Example 6 Example 6 of this invention provides a fully bio-based foaming material, which is prepared by the following method: S1. 93 parts of L-polylactic acid (weight average molecular weight 1.70 × 10⁻⁶) 5 7 parts of cellulose nanocrystal-grafted dextrorotatory polylactic acid (PLA) and g / mol (optical purity 99.1%) were dissolved in chloroform according to the weight ratio and stirred thoroughly. The solvent was then removed at 50 °C to obtain a polylactic acid / cellulose nanocrystal composite material. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 200 °C and 15 MPa to obtain a sheet with a thickness of 2.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 10 MPa, heat it to 175 ℃ for saturation treatment for 10 min, then cool it down to 105 ℃ at a rate of 20 ℃ / min, and immediately depressurize it to atmospheric pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0059] The preparation method of cellulose nanocrystal grafted with dextrorotatory polylactic acid as described in Example 6 of this invention is as follows: (1) Cellulose nanocrystals (aspect ratio of 20) and dextrorotatory lactide were uniformly dispersed in toluene at a weight ratio of 1:10. After the two solutions were mixed evenly, stannous isooctanoate catalyst (1.5% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 80 °C under nitrogen protection for 24 h. The reaction was then completed. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanocrystal grafted dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 15.9 wt%.

[0060] Comparative Example 1 (Pure PLA) S1. L-polylactic acid (weight-average molecular weight 1.70 × 10⁻⁶) 5 A polylactic acid solution was obtained by dissolving polylactic acid (g / mol, optical purity 99.1%) in chloroform and stirring thoroughly. The solvent was then removed at 30 °C to obtain the polylactic acid material. S2. The obtained polylactic acid material is placed in a flat vulcanizing machine and molded at 190 °C and 10 MPa to obtain a sheet with a thickness of 1.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 10 MPa, heat it to 165 ℃ for saturation treatment for 10 min, then cool it down to 110 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to normal pressure at a rate of 30 MPa / s to foam it, thus obtaining polylactic acid foam material.

[0061] Figure 1 This is a scanning electron microscope (SEM) image of the pure polylactic acid foam material prepared in Comparative Example 1 of this invention.

[0062] Comparative Example 2 (Unmodified cellulose nanocrystals) S1. 98 parts of L-polylactic acid (weight average molecular weight 1.70 × 10⁻⁶) 5 Polylactic acid (PLA) / cellulose nanocrystal composite material was obtained by dissolving 2 parts of cellulose nanocrystals (aspect ratio 20) and 2 parts of cellulose nanocrystals (g / mol, optical purity 99.1%) in chloroform according to the weight ratio and stirring thoroughly. The solvent was then removed at 30 °C. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 190 °C and 10 MPa to obtain a sheet with a thickness of 1.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 10 MPa, heat it to 165 ℃ for saturation treatment for 10 min, then cool it down to 110 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to normal pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0063] Comparative Example 3 (Cellulose nanocrystals were replaced with cellulose nanofibers) S1. 98 parts of L-polylactic acid (weight average molecular weight 1.70 × 10⁻⁶) 5 Polylactic acid (PLA) grafted with cellulose nanofibers (g / mol, optical purity 99.1%) and 2 parts by weight were dissolved in chloroform and stirred thoroughly. The solvent was then removed at 30 °C to obtain a polylactic acid / cellulose nanofiber composite material. S2. The obtained polylactic acid / cellulose nanofiber composite material was placed in a flat vulcanizing machine and molded at 190 °C and 10 MPa to obtain a sheet with a thickness of 1.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 10 MPa, heat it to 165 ℃ for saturation treatment for 10 min, then cool it down to 110 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to normal pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0064] The preparation method of cellulose nanofiber grafted with dextrorotatory polylactic acid as described in Comparative Example 3 of this invention is as follows: (1) Cellulose nanofibers (aspect ratio of 100) and dextrorotatory lactide were uniformly dispersed in toluene at a weight ratio of 1:10. After the two solutions were mixed evenly, stannous octoate catalyst (2% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 80 °C under nitrogen protection for 24 h. The reaction was then completed. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanofiber grafted with dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 20.8 wt%.

[0065] Comparative Example 4 (the aspect ratio of cellulose nanocrystals is 10). S1. 98 parts of L-polylactic acid (weight average molecular weight 1.70 × 10⁻⁶) 5 Two parts of cellulose nanocrystal-grafted dextrorotatory polylactic acid (PLA) with an optical purity of 99.1% (g / mol) and cellulose nanocrystal grafted dextrorotatory polylactic acid were dissolved in chloroform according to the weight ratio and stirred thoroughly. The solvent was removed at 30 °C to obtain a polylactic acid / cellulose nanocrystal composite material. S2. The obtained polylactic acid / cellulose nanocrystalline composite material was placed in a flat vulcanizing machine and molded at 190 °C and 10 MPa to obtain a sheet with a thickness of 1.5 mm. S3. Place the obtained sheet in carbon dioxide gas at a pressure of 10 MPa, heat it to 165 ℃ for saturation treatment for 10 min, then cool it down to 110 ℃ at a rate of 10 ℃ / min, and immediately depressurize it to normal pressure at a rate of 30 MPa / s to foam it, thus obtaining a fully bio-based foamed material.

[0066] The preparation method of cellulose nanocrystal grafted with dextrorotatory polylactic acid as described in Comparative Example 4 of this invention is as follows: (1) Cellulose nanocrystals (aspect ratio of 10) and dextrorotatory lactide were uniformly dispersed in toluene at a weight ratio of 1:10. After the two solutions were mixed evenly, stannous octoate catalyst (2% of the weight fraction of dextrorotatory lactide) was added. The reaction was carried out at 80 °C under nitrogen protection for 24 h. The reaction was then completed. (2) The reaction product was dissolved in chloroform and purified by centrifugation to obtain cellulose nanocrystals grafted with dextrorotatory polylactic acid, wherein the grafting rate of dextrorotatory polylactic acid was 21.2 wt%.

[0067] The expansion ratio, large pore size, small pore size and pore density of the fully bio-based foam materials prepared in Examples 1-6 and Comparative Examples 1-4 of this invention are shown in Table 1.

[0068] The thermal conductivity, crystallinity, specific compression modulus, and heat resistance temperature of the fully bio-based foam materials prepared in Examples 1-6 and Comparative Examples 1-4 of this invention are shown in Table 2.

[0069] Table 1. Expansion ratio, large pore size, small pore size, and pore density of the fully bio-based foam materials prepared in Examples 1-6 and Comparative Examples 1-4 of this invention. Table 2. Thermal conductivity, crystallinity, specific compression modulus, and heat resistance temperature of the fully bio-based foam materials prepared in Examples 1-6 and Comparative Examples 1-4 of the present invention. As shown in Comparative Example 1 provided by this invention, when pure polylactic acid is used to prepare foamed materials, the low melt strength and poor foaming performance result in a relatively low foaming ratio (15.2 times), leading to high thermal conductivity and poor thermal insulation performance. Furthermore, the pure polylactic acid foamed material has a relatively large cell size (390.6 μm; cell structure see...). Figure 1 The cell density is relatively low (3.2 × 10⁵ cells / cm²). 3 Meanwhile, due to the slow crystallization rate of polylactic acid, the crystallinity of the foamed material is low (28.7%), resulting in a low specific compression modulus and heat resistance temperature, only 52.1 MPa / g·cm⁻¹. 3 and 85℃.

[0070] Data from Comparative Example 2 provided by this invention shows that when unmodified cellulose nanocrystals are added, the expansion ratio of the polylactic acid / cellulose nanocrystal composite foam is actually lower than that of pure polylactic acid foam. This is because the cellulose nanocrystals undergo severe agglomeration in the polylactic acid matrix, preventing them from effectively improving the melt strength of polylactic acid. Furthermore, the presence of interfacial gaps allows carbon dioxide gas to escape more easily, thus reducing the expansion ratio and consequently decreasing the thermal insulation performance. Due to the severe agglomeration of cellulose nanocrystals and weak interfacial forces, their improvement on the crystallinity and mechanical properties of polylactic acid is limited, resulting in the heat resistance temperature and specific compression modulus of the obtained foam material only increasing to 95 °C and 75.4 MPa / g·cm, respectively. 3 .

[0071] As can be seen from Comparative Examples 1 and 2 provided by this invention, when only pure polylactic acid or only unmodified cellulose nanocrystals are added, due to the lack of graft modification effect of dextrorotatory polylactic acid on cellulose nanocrystals, stereocomposite crystals cannot be generated at the interface between polylactic acid and cellulose nanocrystals. The nucleation site is singular, and only a single large-sized cell is generated. The improvement of the mechanical properties of foamed materials by small-sized cells is lacking. At the same time, the advantages of stereocomposite crystals in promoting the dispersion of cellulose nanocrystals and enhancing interfacial forces cannot be effectively utilized, thus limiting the reinforcing effect of cellulose nanocrystals on polylactic acid.

[0072] As shown in Comparative Example 3 provided by this invention, although the bio-based foamed material obtained by grafting dextrorotatory polylactic acid (PLA) onto a levorotatory PLA matrix with cellulose nanofibers and then foaming it has a bimodal pore structure, its foaming ratio is only 20.3 times. Therefore, its thermal insulation performance is significantly inferior to that of the foamed material prepared in the embodiments of this invention. This is because, compared to cellulose nanocrystals, cellulose nanofibers have a much longer aspect ratio, making them prone to forming a network structure, thus limiting the foaming ratio of PLA.

[0073] As can be seen from Comparative Example 4 provided by the present invention, when cellulose nanocrystals with a small aspect ratio (such as an aspect ratio of 10) are used for modification, the melt strength of polylactic acid is not sufficiently enhanced, causing the cells to break or merge during growth, which is insufficient to support the growth of the cell structure and limits the improvement of the foaming ratio.

[0074] Therefore, when the present invention first grafts dextrorotatory polylactic acid onto the surface of cellulose nanocrystals with a suitable aspect ratio ( Figure 2 The infrared spectrum showed that the cellulose nanocrystals grafted with dextrorotatory polylactic acid (PLA) exhibited carbonyl peaks belonging to PLA, proving the successful grafting of PLA. When this graft was blended with a levorotatory polylactic acid (PLA) matrix, the PLA on the surface of the cellulose nanocrystals formed stereocomposite crystals distributed at the interface with the levorotatory PLA matrix in situ. The dual nucleation effect of the stereocomposite crystals and the cellulose nanocrystals resulted in a bimodal distribution of pore size in the prepared foam material. A suitable aspect ratio can increase the foaming ratio. The combination of the bimodal pore structure and the high foaming ratio endowed the foam material with high thermal insulation and mechanical properties.

[0075] Moreover, the presence of stereocomposite crystals can significantly improve the dispersion of cellulose nanocrystals, effectively increase the melt strength and crystallization rate of polylactic acid, and enhance the interfacial forces between the polylactic acid matrix and cellulose nanocrystals. This allows cellulose nanocrystals to significantly increase the specific compression modulus of polylactic acid foam materials, thereby improving their mechanical properties.

[0076] It is evident that the fully bio-based foamed material prepared by this invention possesses high foaming ratio, thermal insulation performance, heat resistance performance, and specific compression modulus, and can be widely used in food packaging, building materials, and other fields.

Claims

1. A method for preparing a fully bio-based foamed material, characterized in that, include: S1. Dissolve 90-99 parts of L-polylactic acid and 1-10 parts of cellulose nanocrystal-grafted D-polylactic acid in organic solvent a according to the weight ratio, stir thoroughly, and desolvent at 20-80 °C to obtain polylactic acid / cellulose nanocrystal composite material, wherein the aspect ratio of the cellulose nanocrystal is 15-30. S2. The polylactic acid / cellulose nanocrystalline composite material is placed in a flat vulcanizing machine for compression molding to obtain a sheet; S3. Place the sheet in carbon dioxide gas, heat it to the saturation temperature for saturation treatment, then cool it to the foaming temperature, and immediately depressurize it to normal pressure for foaming to obtain the fully bio-based foamed material.

2. The method for preparing the all-bio-based foamed material according to claim 1, characterized in that, In step S1, according to the weight ratio, the amount of L-polylactic acid is 97-98.5 parts, and the amount of cellulose nanocrystal grafted with D-polylactic acid is 1.5-3 parts.

3. The method for preparing the all-bio-based foamed material according to claim 1, characterized in that, In step S1, the weight-average molecular weight of the L-polylactic acid is 5 × 10⁻⁶. 4 ~5×10 5 g / mol, optical purity ≥97%.

4. The method for preparing the all-bio-based foamed material according to claim 1, characterized in that, In step S3, the pressure of the carbon dioxide gas is 5~25 MPa, the saturation temperature is 150~190 ℃, the saturation time is 3~30 min, and the foaming temperature is 80~130 ℃.

5. The method for preparing the all-bio-based foamed material according to claim 1, characterized in that, In step S3, during the process of cooling from the saturation temperature to the foaming temperature, the cooling rate is 2~30 ℃ / min.

6. The method for preparing the all-bio-based foamed material according to claim 1, characterized in that, In step S3, the depressurization rate of the depressurization foaming is 5~60 MPa / s.

7. The method for preparing the all-bio-based foamed material according to claim 1, characterized in that, In step S1, the method for preparing the cellulose nanocrystals grafted with dextrorotatory polylactic acid includes: (1) Cellulose nanocrystals and dextrorotatory lactide were uniformly dispersed in organic solvent b at a weight ratio of 1:3 to 1:

30. After being mixed evenly, a catalyst was added. The reaction temperature was 70 to 110 °C, and the reaction was carried out under nitrogen protection for 12 to 36 h to obtain the reactants. (2) Dissolve the reactants in chloroform and purify by centrifugation to obtain the cellulose nanocrystal grafted dextrorotatory polylactic acid.

8. The method for preparing the all-bio-based foamed material according to claim 7, characterized in that, In step (1), the catalyst is stannous octoate or stannous isooctanoate, and the amount of the catalyst used is 0.5% to 4% of the weight fraction of dextrorotatory lactide.

9. A fully bio-based foamed material prepared by the method of preparing a fully bio-based foamed material according to any one of claims 1-8.

10. The fully bio-based foamed material according to claim 9, characterized in that, The thermal conductivity of the all-bio-based foam material is 31~36 mW·m. -1 ·K -1 The specific compression modulus is 150~220 MPa / g·cm. 3 .

Citation Information

Patent Citations

  • A method for preparing a cellulose nanocrystal-reinforced polylactic acid foam material

    CN107383434B

  • Thermal insulation foam material with bimodal pore structure and preparation method thereof

    CN116178777B